Kedudukan Perjanjian Terapeutik sebagai Perikatan Upaya (Inspanningsverbintenis) dan Batas Pertanggungjawaban Medis di Indonesia - Emi Silvia; Iwan Iryansyah Setiawan; Sari Marlia; Tio Setiawan; Afrizal; Ahmad Affendi; Syafrida (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Therapeutic agreements are legal relationships between medical personnel and patients that are the basis for the implementation of medical actions in health services. Although doctrinally qualified as an engagement of efforts (inspanningsverbintenis), in practice there are still differences of understanding between medical personnel and patients that often lead to disputes regarding the limits of medical liability. This study aims to analyze the position of therapeutic agreements as an engagement effort and formulate the limits of medical liability in the Indonesian legal system. The research method used is normative legal research with a legislative approach, a conceptual approach and a case approach. The legal materials used consist of primary, secondary and tertiary legal materials that are analyzed juridically qualitatively. The results of the study show that therapeutic agreements are basically an engagement of efforts that require medical personnel to make their best efforts according to professional standards, service standards and operational procedure standards without guaranteeing patient recovery. The validity of the therapeutic agreement is largely determined by the fulfillment of informed consent as a form of patient consent that is given consciously after obtaining adequate information. Failure to perform medical procedures does not necessarily give rise to legal liability if the action has been carried out in accordance with professional standards and the principles of prudence. The limit of medical liability is determined based on deviations from professional standards, negligence, or violation of patient rights, which can lead to civil, criminal, administrative, or ethical consequences. Therefore, it is necessary to affirm the concept of commitment and optimize the implementation of informed consent in order to realize legal certainty and balanced protection for medical personnel and patients.